Early Marriage among Adolescent Boys and Young Men in Urban Informal Settlements of Bangladesh - Biswas, Subas; Azmi, Raia; Mowri, Seama; Ahsan, Sairana; Sultana, Rafia; Rashid, Sabina F. (Young Lives, 2022)
This book chapter was published in the book named Dreaming of a Better Life Child Marriage Through Adolescent Eyes and the definite version is available at : https://www.younglives.org.uk/sites/www.younglives.org.uk/files/YL-DreamingOfBetterLife-LowRes_0.pdf